Does equal education opportunity apply to undocumented children in Sabah? An assessment of the national education policy / Emmy Liew and Firdausi Suffian - Liew, Emmy; Suffian, Firdausi (2021)
Education is a basic human right. Regardless of one’s “race, color, sex, language, religion, political or another opinion, national, ethnic or social origin, property, disability, birth or another status”. As the statement speaks, it illustrates how important education is until it is elevated as a basic human right. Deprivation to education is the deprivation of basic human rights. Among the major importance of education is for personal empowerment, social inclusion, economic development, and building a national identity. In terms of personal empowerment, the knowledge, wisdom, and understanding human beings gain through education help to heighten human decency. In terms of social inclusion, it helps the migrants to assimilate with the local community, understanding the culture, and respecting the laws of the host country, which breeds stability and peace. In terms of economic development, a knowledgeable worker will have a better understanding of the tasks he is responsible for, make a more informed decision on the resources allocated, be motivated to initiate innovation, and communicate efficiently.